Vertical crustal motion of active plate convergence in Taiwan derived from tide gauge, altimetry, and GPS data - Chang, Emmy T.Y.; Chao, Benjamin F.; Chiang, Chieh-Chung; Hwang, Cheinway (Tectonophysics, 2012)
Located at the converging junction between the Eurasian and Philippine Sea plates, the island of Taiwan is subject to an active lithospheric deformation as well as seismicity. Taking the difference between the satellite altimetry data (ALT) that give the absolute sea level variation and the tide gauge data (TG) that record the relative sea level variation, we obtain the absolute vertical crustal motion of the tide gauge sites. We use 20 TG stations along the west and east coasts of Taiwan along with the ALT measurements from the TOPEX/Poseidon–Jason satellites in the nearby waters. The ALT–TG results are compared with vertical GPS measurements in discussing vertical motion. We find a general subsidence of the entire Taiwan coast during the past two decades. The west coast sees no prominent vertical motion but with a severe local subsidence due to the over-withdrawal of groundwater. On the east coast, the ALT–TG results in the northern section demonstrate a northward dipping motion. The elastic thickness of the neighboring oceanic lithosphere modeled as an elastic plate with the flexure of the subducting plate shows that the adjacent Philippine Sea plate should be an old, thick oceanic plate, which could drag the slab into the mantle as manifested in a gentle northward subsidence in the northeast Taiwan. In the southern section of the east coast, the ALT–TG results reveal a segmented or undulating pattern in the vertical-motion rates. Judging from the different behaviors between the co-seismic and interseismic vertical motions marked by the major earthquakes during the studied period, we postulate a temporal saw-tooth scenario for the deformation in phases. It demonstrates the opposite motions under different mechanisms in the frontal sections of the subduction zone, which can be understood with lateral collision and slab dragging subject to varied temporal and spatial dependences. ► We study Taiwan’s vertical motion by analyzing TG and the nearby ALT measurements. ► Our results show the varied tectonic influences for the east and west Taiwan. ► The east coast exhibits a segmented pattern in plate convergence. ► A saw-tooth scenario is used to explain the co- and inter-seismic motion phases.